Insider trading in a macroeconomic crisis : Evidence from the Finnish stock market during COVID-19 pandemic - Ruska, Henrik (My University, 2024)
COVID-19 pandemic had a significant impact on the global stock markets. The spreading of the virus launched a global stock market crash in the beginning of 2020, which was followed by a swift recovery in stock prices during the rest of the year. The market uncertainty level remained elevated after the crash at least until the first quarter of 2021. At the same time, corporate insiders are believed to be the most informed investors in the market. By examining the changes in their trading patterns and trading profitability during the crisis, a better understanding of the reasons and effects of the market turbulence can be achieved. The purpose of the study is to analyse the effects of COVID-19 pandemic to insider trading in the Finnish stock market. The specific focus areas are the stock market crash of 2020 and the effect of COVID-19 related uncertainty on the short-term profitability of insider trading. The insider trading sample used in the thesis is limited to the companies listed in the main list of Nasdaq Helsinki during the three-year sample period from 2019 to 2021. Previous research has found that insider trading during stock market crashes can be indicative of the post-crash returns of the companies. Moreover, macroeconomic crises have previously found to have an impact on the short-term profitability of insider trading. The results of the thesis show that the number of insider purchases peaked during the market crash of 2020, which indicates that insiders perceived the crash as a lucrative opportunity to increase the ownership stakes in their companies. However, other insider trading measures did not show similar significant changes during the crash. The changes in the insider trading during the crash are also indicative of the 6-month post-crash returns, although these results suffer from robustness issues caused by small sample size and multicollinearity. The results are inconclusive on whether the primary motive for insider trading during the crash was financial gain or signalling. Regarding the short-term profitability of insider trading, only insider sales are followed with significant abnormal returns during the sample period. On the other hand, the COVID-19 related uncertainty affects only the profitability of insider purchases as abnormal returns following acquisitions are significantly lower during the crisis. This is due to the highly significant and negative returns after purchases during the market crash of 2020. The results imply that COVID-19 did not increase the information advantage of the insiders at least when measured with relatively short 21-day event windows. Lastly, trades by CEOs and CFOs appear to be more profitable in the short-term compared to other insider groups depending on details of the regression models used. The results also suggest that the profitability differences between insiders might be affected by macroeconomic crises.

Koronaviruspandemia vaikutti merkittävästi maailman osakemarkkinoihin. Viruksen leviäminen käynnisti vuoden 2020 alussa maailmanlaajuisen pörssiromahduksen, jota seurasi osakekurssien nopea elpyminen loppuvuoden aikana. Markkinoilla koettu epävarmuus pysyi romahduksen jälkeen kohonneella tasolla ainakin vuoden 2021 ensimmäiselle kvartaalille saakka. Toisaalta yrityksen sisäpiiriin kuuluvien henkilöiden uskotaan olevan markkinoiden parhaiten informoituja sijoittajia. Tarkastelemalla kriisin aikana tapahtuneita muutoksia sisäpiirin kaupankäynnissä ja sen kannattavuudessa voidaan ymmärtää paremmin markkinoiden epävakauden syitä ja seurauksia. Tutkimuksen tavoitteena on analysoida COVID-19-pandemian vaikutuksia sisäpiirikaupankäyntiin Suomen osakemarkkinoilla. Tutkimuksen painopistealueina ovat vuoden 2020 pörssiromahdus ja koronaviruspandemiaan liittyvän epävarmuuden vaikutus sisäpiirikaupan lyhyen aikavälin kannattavuuteen. Tutkielmassa käytettävä sisäpiirikauppojen otos on rajattu koskemaan Nasdaq Helsingin päälistalla noteerattuja yhtiöitä kolmen vuoden tutkimusperiodin aikana 2019–2021. Aiemmissa tutkimuksissa on havaittu, että sisäpiirikauppa pörssiromahdusten aikana ennakoi yhtiöiden romahduksen jälkeisiä tuottoja. Lisäksi makrotaloudellisten kriisien on aiemmin havaittu vaikuttavan sisäpiirikaupan lyhyen aikavälin kannattavuuteen. Tutkielman tulokset osoittavat, että sisäpiirin tekemien osakeostojen määrä oli korkeimmillaan vuoden 2020 markkinaromahduksen aikana, mikä viittaa siihen, että sisäpiiriläiset pitivät romahdusta hyvänä ostopaikkana. Muut sisäpiirikaupan aktiivisuutta kuvaavat muuttujat eivät kuitenkaan osoittaneet samanlaisia tilastollisesti merkitseviä muutoksia romahduksen aikana. Muutokset sisäpiirikaupankäynnissä romahduksen aikana ennakoivat myös romahduksen jälkeisiä kuuden kuukauden tuottoja, vaikka näiden tulosten luotettavuus kärsiikin pienestä otoskoosta ja multikollineaarisuudesta. Tulokset eivät ole yksiselitteisiä sen suhteen, oliko sisäpiirikaupan ensisijainen motiivi kriisin aikana taloudellisen hyödyn tavoittelu vai signalointi. Sisäpiirikaupan lyhyen aikavälin kannattavuuden osalta voidaan todeta, että ainoastaan sisäpiirin myynneistä seuraa tilastollisesti merkitseviä epänormaaleja tuottoja tutkimusperiodin aikana. Koronavirukseen liittyvä epävarmuus sen sijaan vaikuttaa ainoastaan sisäpiirin ostojen kannattavuuteen, sillä ostojen jälkeiset epänormaalit tuotot ovat kriisin aikana tilastollisesti merkitsevästi pienempiä. Tämä johtuu vuoden 2020 markkinaromahduksen aikaisten osakeostojen erittäin merkitsevistä negatiivisista tuotoista. Tulokset osoittavat, että koronaviruspandemia ei lisännyt sisäpiiriläisten informaatioetua markkinoilla ainakaan, jos kannattavuutta mitataan suhteellisen lyhyillä 21 päivän tapahtumaikkunoilla. Lisäksi toimitusjohtajien ja talousjohtajien tekemät kaupat näyttävät olevan lyhyellä aikavälillä kannattavampia kuin muiden sisäpiiriläisten tekemät kaupat riippuen hieman käytettyjen regressiomallien yksityiskohdista. Tulokset antavat myös viitteitä siitä, että makrotaloudelliset kriisit saattavat vaikuttaa sisäpiiriläisten välisiin kannattavuuseroihin.
Keywords: Insider trading, COVID-19, coronavirus, pandemic, macroeconomic crisis, insider trading profitability, information asymmetry, signalling, sisäpiirikaupankäynti, COVID-19, koronavirus, pandemia, makroekonominen kriisi, sisäpiirikaupankäynnin kannattavuus, epäsymmetrinen informaatio, signalointi